CRISPR/Cas13a combined with reverse transcription and RPA for NoV GII.4 monitoring in water environments - Yiqiang Sun; Weiwei Zhang; Houyun Zhang; Feng Zhao; Laijin Su (Environment International)
Water bodies contaminated with the norovirus (NoV) are important vectors for its transmission. Therefore, enhanced monitoring of NoV in aqueous environments plays an active role in preventing diseases. Here, we reverse transcribed viral RNA into cDNA, and then used the constructed RPA-CRISPR/Cas13a-based platform for sensitive and quantitative monitoring of NoV GII.4 in aqueous environments. The use of glycerol as a phase separator and the direct release of nucleic acids from the virus by NaOH significantly enhanced the stability of the assay and reduced its economic cost. This assay is sensitive, specific, and stable. Based on the qualitative detection method, we established a relatively accurate quantitative detection method using the plasmid as a standard. Four water samples, totaling 64 samples, were analyzed using this method and compared with the qPCR method. The results of the two methods showed 100 % concordance with no significant difference in viral load. The entire process of our established method—from viral nucleic acid extraction to the output of the results—was completed in 30 min, much less than the time required for qPCR method. This suggests that the assay can be used as an alternative to qPCR for monitoring the change of NoV GII.4 concentration in water bodies, and shows high potential for application in the immediate detection of viruses in aqueous environments and resource-limited areas.